PENGOLAHAN LIMBAH TEKSTIL (METHYLENE BLUE) MENGGUNAKAN ADSORBEN KARBON AKTIF KULIT MANGGIS (GARCINIA MANGOSTANA) TERAKTIVASI HIDROGEN PEROXIDE - Suhirman Suhirman; Rizky Ibnufaatih Arvianto; Arfando Yudha Pradana; Panji Wijaya (Fakultas Teknik Universitas Wahid Hasyim, 2025)
Textile wastewater is a major contributor to aquatic pollution because synthetic dyes such as Methylene Blue (MB) are toxic, persistent, and resistant to biodegradation. This study investigates the adsorption performance of activated carbon derived from mangosteen peel (Garcinia mangostana) activated with hydrogen peroxide (H₂O₂) for MB removal from aqueous solution. Activated carbon was prepared by carbonization at 850 °C, followed by chemical activation with diluted 50% H₂O₂. Adsorption tests were performed using 50 mg of adsorbent in 250 mL of MB solution (50 ppm) for 120 min, and residual concentrations were determined by UV–Vis spectrophotometry at 663 nm. H₂O₂ activation enhanced the specific surface area from 522 to 700 m²/g and enriched oxygen-containing functional groups (–OH, C=O) on the carbon surface. The contact angle decreased from 134,01° to 55,83°, indicating improved hydrophilicity. The activated carbon achieved 68% MB removal, significantly higher than the non-activated carbon (16%). Adsorption kinetics were well described by the pseudo-second-order model, with a high determination coefficient (R² = 0.988).